Program Seleksi Beasiswa PPA dan BBP-PPA Berbasis Visual Basic 6.0 di Universitas Surakarta - Anggi Supriadi; Cicilia Puji Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
PPA and BBP-PPA scholarship admissions process at the University of Surakarta still use the Microsoft Excel-based input and output. So that the selection process for this scholarship have a disadvantage in terms of the use of time, energy efficiency and the mind. Based on these data I was motivated to create an application using Microsoft Visual Basic 6.0 with Microsoft Access 2010 database. The application created using Microsoft Visual Basic 6.0 as a form in the data input, the selection process and output display selection results scholarships and Microsoft Access 2010 is used as a data storage medium students who stored for later data that has been stored can be displayed in accordance boundary data will be used. Display accurate data contains a combination of the basic criteria to qualify for the scholarship acceptance of the existing data on student data and student family data. At the time of running the program in the community scholarship selection Surakarta University, scholarship acceptance processes BBP-PPA and PPA from data collection, input, process and output data will be more efficient time, the effectiveness of energy and mind. The selection process starts automatically based on criteria that are needed, so that the displayed data will be more accurate, and reading the data easier to understand.